Atoms, energy and machines - McCormick, Jack.; American Museum of Natural History ([Mankato, Minn.: Creative Educational Society, 1967)
Explains the basic concepts of measurement, motion, and the structure of matter and other aspects of chemistry and physics.
Published in cooperation with the American Museum of Natural History.
Keywords: Science -- Juvenile literature; Physics; Chemistry